The role of bone ring technique for bone augmentation in implant surgery, a review - Madiha Khan; Shizrah Jamal; Robia Ghafoor (Journal of the Pakistan Medical Association, 2024)
Bone grafting with simultaneous implant placement using the novel bone ring technique was a procedure introduced with the intention of three-dimensional bone augmentation with simultaneous implant placement in both maxilla and mandible. A ring-shaped bone is placed in the socket, which is secured by an implant placed through the ring. The current narrative review was planned to provide a concise summary of the core concepts surrounding bone augmentation, to provide context for understanding the bone ring technique, and to highlight the basics of bone grafting and the origin of the technique to its advancement and its importance in the light of current literature. Key Words: Dental implants, Bone augmentation, Bone grafting, Guided bone regeneration.